A Mapping of the Physical and Electrochemical Properties of Composite Lithium-Ion Batteries Anodes Made from Graphite, Sn, and Si - Smrekar, Sacha (2020)
Nowadays, there is an evident need to improve the current Li-ion battery systems, in order to make them more reliable, durable and safe. Regarding this objective, the application of composite materials –based mainly on the combination of Si, Sn and carbon– appears as a very promising alternative for future anode materials. However, despite the great amount of publications dealing with this topic, there is not a systematic study that allows interpreting and understanding how the combination of these materials affects the electrochemical performance of the anodes prepared with them. In light of this need, in this work we propose a straightforward ball-milling procedure to prepare Sn/Si/graphite composites with different mass proportions of each material. For all compositions, a systematic study was performed in order to determine how each material affects the specific capacity, capacity fading and stability towards a change in loading current. We found that the material prepared with Sn33Si33C33 appears to be the most promising one, delivering a reversible capacity of 906.9 mAh g−1 even after 120 cycles at 0.5 A g−1, thus encouraging the development of new composites based on these materials for industrial applications.